THE STUDY OF DEIXIS USED BY THE MAIN CHARACTERIN THE IRON MAN 3 MOVIE DIALOGUE - BRAMANTA, BAGUS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Deixis, Person Deixis, Place Deixis, Time Deixis, Social Deixis, Discourse Deixis, Movie. Deixis is a study about language phenomena which discusses words that have a relative meaning. Deixis can be found in the spoken and written language. In this study, the writer intends to analyze deixis contained in Iron Man 3 movie dialogue. This study is conducted to find out: (1) types of deixis used by Tony Stark character in the movie Iron Man 3: (2) meaning of deixis used by Tony Stark character in the Movie Iron Man 3. The writer uses Levinson’s theory about deixis and Cook’s theory about context in analyzing the data.This is a qualitative study since this research has the characteristics of qualitative research, such as natural setting, human instrument, inductive data analysis, descriptive discussion and focus more on process than the result. The data of this study were taken from Tony Stark utterances, the main character of Iron Man 3.In this study the writer found 91 deictic expressions in the movie transcript. Through the analysis using Levinson’s theory, the writer found 64 person deixis, 6 place deixis, 1 time deixis, 1 social deixis and 19 discourse deixis. The types of deixis most commonly found is third person deixis because Tony Stark often talks about other people. The second goes to discourse deixis that used to connect the previous discourse to the surrounding utterances to make the utterances clear. The first person deixis was used once in Tony’s utterances. The second person deixis was used to indicate the reference to one or more addressee. It was an addressee or the hearer of the speaker. Place deixis was used to describe a location related to the location of the participant in the speech event, as well as the ones that have been shown in the movie. Time deixis appeared when the utterance was produced by the speaker and when event occurs. Social deixis was the marking of social relationship in linguistics expressions which can be shown in the movie. The meaning of deixis that was based on context support, there were co-text and picture of the movie.The writer in this study only analyze the  types of deixis. It is different with pronoun, in which deixis is describes words or expressions of which the reference relies absolutely on context. Meanwhile, a pronoun is used to replace a noun. The next researcher hopefully not only focuses on types of deixis but also analyzes the difference between the deixis and pronoun. Besides, the writer suggests to the further researcher uses the same theory but different in the data source such as, article or in any literary work.